THE IMPACT OF CHILD SEXUAL ABUSE - Aisyah Annisa Pratiwi; Al Asyary (JUMP Health (Journal of Ultimate Public Health), 2017)
Physical, emotional and sexual abuse of children is a major problem in South Africa, with severe negative outcomes for survivors. To date, no known studies have used data directly obtained from community-based samples of children to investigate prevalence, incidence, locations and perpetrators of child abuse victimisation. This study aims to investigate prevalence and incidence, perpetrators, and locations of child abuse victimisation in South Africa using a multicommunity sample.